Manajemen Pendidikan Agama Islam Berbasis Pembelajaran Kreatif di Era Teknologi Digital - Visco Dhiya Salabila (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
the integration of digital technology in Islamic education has been a significant topic of interest. This research explores the impact of technology integration in the management of Islamic education based on creative learning in the digital era. The findings highlight significant benefits in enhancing access to diverse religious content, student interactivity, and the dynamics of interaction between teachers and students. However, challenges such as access disparities, insufficient training for educators, and data privacy issues are focal points of this research. From these findings, several recommendations are provided, emphasizing the importance of educator training, uniform technological infrastructure investment, formulation of supportive policies, and cross-sector collaboration to enhance technology utilization in the context of Islamic education. It is hoped that implementing these suggestions will support the development of a more inclusive and responsive Islamic education in the digital era.